The Mystery of IndoEuropean Languages – a Few Remarks on the Book by Oleg Poljakov - Marczewska, Marzena (Respectus Philologicus, 2016)
Poljakov, Oleg, 2015. The Marvel of Indo-European Cultures and Languages. The Lithuanian Bridge to Indo-European. Vilnius: Vilnius University Publishing House. 637 p.
Keywords: none